Outcomes of a Pilot Intervention Study for Young Adults at Risk for Cardiovascular Disease Based on Their Family History. Issue 5 (September 2016) - Imes, Christopher C.; Dougherty, Cynthia M.; Lewis, Frances Marcus; Austin, Melissa A.
Abstract : Background: Lifestyle choices have a significant impact on cardiovascular disease (CVD) risk. Interventions to promote a heart-healthy lifestyle in young adults at long-term high risk for CVD are needed to decrease the burden of CVD. However, few interventions with this purpose have been developed. Objective: The objective of this study was to examine the effect of a pilot intervention on young adults with a family history of CVD that used 3-generation pedigrees, risk factor information, and counseling on heart disease knowledge, perceived CVD risk, and intention to engage in a heart-healthy lifestyle. Methods: A pretest-posttest design, with within-group analysis, was used to examine the effect of the intervention. Paired t test and Wilcoxon signed rank tests were used to examine the changes in heart disease knowledge, perceived risk, and behavioral intention from baseline to postintervention. The Cohen d was calculated to examine the effect of the intervention on study measures. In addition, Spearman ρ was used to examine the associations between postintervention perceived risk, postintervention behavioral intention, and family history. Results: The sample for the pilot study included 15 mostly white and mostly female healthy young adults between the ages of 18 and 25 years. The intervention was effective at increasing CVD knowledge ( P = .02) and had a medium effect on perceived risk and intention to engage in a heart-healthy lifestyle (Cohen d, 0.48–0.58). There were significant associations between postintervention perceived risk and postintervention intention to exercise and the participants' family history of coronary heart disease ( r = 0.62, P = .014 and r = 0.55, P = .035, respectively). Conclusions: Interventions are needed to increase individuals' awareness of their long-term CVD risk and to improve their ability to make lifestyle changes. Although this intervention was only tested in a small sample, it shows promise to improve heart disease knowledge and perceived lifetime CVD risk and may effect longer-term risk for CVD.